ROBOT WAYANG ANOMAN - , ARYUDHA WICAKSONO, Drs. Abdul Rouf,M.I.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A wayang robot has built which title is Wayang Robot Anoman that walk on the track provided to perform a worship movement that modelled by a wayang character in Javanese culture named Anoman. In every motion controlled by ATMega16 microcontroller in 5 degree of freedom. The system of wayang robot Anoman designed use 2 electric motor system controlled with a microcontroller. The first system is an arm motion system use mini servo. Mini servo attached on 2 arms and 2 elbow that direct connected with microcontroller. While the other system is an addition motion system use DC motor. The motion that mentioned earlier is vertical rotation. To control DC motor needed a motor driver that named L293D IC. This driver will moved DC motor rotation in two direction used high torque ( CW and CCW ) in accordance with input from data output which from microcontroller port that has connected. The result that has been achieved is the tests performed on comparison warrior worship movement with original wayang is has less suitable position at rotation angle of electric motors that used as actuator. Similar results were also shown in the test of monk worship movement. Besides the testing was conducted with lower speed than an original wayang speed because of the fragility in the construction of the wayang robot.